Dimensi Spiritual Terhadap Perilaku Kewargaan Organisasi: Peran Mediasi Kepemimpinan Adaptif dan Kualitas Kehidupan Kerja - Pujianto, Wahyu Eko; Purwono, Rudi; Evendi, Evendi; Supriyadi, Supriyadi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to determine the relationship of the spiritual attachment dimension to adaptive leadership, QWL, and OCB. In addition, adaptive leadership and QWL are variables mediating the relationship of the spiritual attachment dimension to OCB. This research uses a quantitative approach. The population in this study is the Strawberry generation in Sidoarjo, Surabaya, and Gresik, using purposive sampling techniques in determining the sample. The data in this study were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with tools using smartPLS software. The results of this study indicate that the spiritual dimension significantly affects adaptive leadership, the spiritual dimension substantially impacts the quality of work life, and the spiritual size affects organizational citizenship behaviour. In addition, the spiritual dimension also significantly influences organizational citizenship behaviour through adaptive leadership. The spiritual dimension significantly affects organizational citizenship behaviour through the quality of work life in the strawberry generation in Sidoarjo, Surabaya, and Gresik. This research will be a reference for other research in the future with a different context and focus.